Why CEOs need advanced education and training for optimizing decisions in the development of innovative medicinal products? justification and recommendation - Kramer, Peter-Jürgen; Bode, Gerd; Bass, Rolf (Frontiers in Pharmacology, 2024)
Chief executives have been educated and trained how to handle business, to take executive decisions, and take care of financial and human resources in favor of the company they are leading. CEOs (chief executive officers) of innovative pharmaceutical businesses, among others, have only seldomly been trained to understand the immense time periods involved between decisions and their moment of impact, and the skills and languages used by their internal and external R&D (research and development) staff. R&D staff and regulators, however, have undergone full training, and are usually capable of understanding each other across their various specialties (among them compound finding, quality, safety, efficacy, efficiency, risk assessment and management). What is lacking is the specialized training of CEOs in sectors of R&D, which would benefit the company and patients alike. We propose that CEOs and upper management should undergo cross-border training in R&D topicswherever possible across all sectors, but minimally to grasp such topics sufficiently to handle those scenarios demanding immediate decisions (be it the CEO cutting off developments, or R&D experts defending their continuation). Learning the language of regulators and R&D scientists will help CEOs to take better decisions.Training programs for R&D staff have been developed and implemented all over Europe and elsewhere. We propose to work with the PharmaTrain3.0 Syllabus (www.pharmatrain.eu/pharmatrain-syllabus) (for details see supplementary material), which would support clear-cut training of relevant topics by competent teaching staff towards certification of CEOs and high management.It is foreseen that understanding the language and comprehending the R&D issues and staff will help CEOs in achieving reasoned decisions. It is expected that such decisions will incorporate not only the reasons seen for discontinuation of R&D programs, but also those reasons, which favor their continuation under the same or different headlines (e.g. changing the initially proposed indication).Taken together, training according to "Good Training Practices" (GTP) will benefit the company and the patient, who will receive better medicines as early as possible.